DETEKSI BRUCELLOSIS PADA SAPI PERAH PERANAKAN FRIESIAN HOLSTEIN DI KECAMATAN PAGU KABUPATEN KEDIRI - ady kurnianto; Bagus Uda Palgunadi; Roeswandono Roeswandono; Adilla Luthfita Fa’za (VITEK : Bidang Kedokteran Hewan, 2019)
Brucellosis (Keluron disease) is a strategic infectious disease with zoonotic potential, one of which is genus Brucella abortus. This research aims to detect Brucellosis in dairy cattle FH in Pagu District, Kediri Regency. This research uses two serological tests, namely the Rose Bengal Test (RBT) and the Complement Fixation Test (CFT) with descriptive analysis method. 30 cattle blood samples were taken from the coccigea vein. The blood was set aside at room temperature to form a serum. The serum that has been obtained is taken to the Department of Food and Livestock of Kediri Regency for checking the RBT. The remaining serum obtained was sent to BBVet Wates for CFT examination. The results obtained show negative results on both tests. But one of the samples with the code S9 had gone through an abortion. This might occur due to other factors such as genetic disorders, the presence of viruses such as BVD, toxic agents and live vaccines during pregnancy.